Festival Durian sebagai Penguatan Ekonomi dan Identitas Budaya Lokal: Studi Pustaka pada Tradisi Tahunan di Klaten - Danang Vanamai; Taufikur Rohman (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the role of the Durian Festival in Klaten Regency as an instrument for strengthening the local economy and cultural identity of agrarian communities. The research employs a qualitative approach using a library research method through the review of scholarly literature, academic books, media publications, and relevant institutional documents. The selection process adopted the PRISMA principles to ensure systematic and credible data collection. Data were analyzed using descriptive-analytical content analysis. The findings indicate that the Durian Festival functions not only as a harvest celebration but also as a medium for preserving communal values such as mutual cooperation, symbolizing agricultural abundance, and reinforcing the village’s identity as a durian-producing area. From an economic perspective, the festival creates business opportunities for farmers and MSMEs through increased trade activities and a multiplier effect during the event. Within the framework of gastronomy tourism and event management, the festival holds potential to be developed as a sustainable community-based tourism product. With more strategic and participatory management, the Klaten Durian Festival can serve as a model for cultural tourism development that supports economic self-reliance and the preservation of local identity.